Cross-lingual Transfer of Literacy Skills Among Pupils Speaking Same and Different Home and School Languages - Danieles-Cortez, Antoniette A. (Alipato, A Journal of Basic Education, 2022)
This study sought to (1) investigate whether cross-lingual transfer occurs in the vocabulary knowledge (VK) and listening comprehension (LC) skills of pupils with the same home and school language (SHSL) and pupils with different home and school languages (DHSL) and (2) identify which skills are transferable across languages. Quantitative data were collected through the Vocabulary Knowledge Test (VKT) and Listening Comprehension Test (LCT) in Hiligaynon, Filipino, and English. These were pilot tested with two groups of Grade 1 pupils comparable with the actual participants. Data gathering covered three grading periods following the Department of Education academic calendar. The t-test was used to determine which group performed better in the VKT and LCT in MT-Hiligaynon, Filipino, and English. Data analysis revealed that VK sub-concepts and LC skills can be transferred across languages. The SHSL group performed better than the DHSL group in MT- Hiligaynon and English VK while DHSL pupils performed better than the SHSL pupils in Filipino VK. In the LCT, the SHSL pupils performed better than the DHSL pupils when the data were treated inferentially. Based on these findings, it can be inferred that home language is not the only major variable in learning other languages after the L1. Keywords: cross-lingual transfer, MTB-MLE, Literacy  Skills